Peranan penegak hukum terhadap tindak pidana prostitusi online dalam peradilan pidana di Indonesia (studi kasus di Daerah Istimewa Yogyakarta) - Aldino Perdana Guntar; Fransisca Romana Harjiyatni; Eko Nurhayanto (Kajian Hasil Penelitian Hukum, 2020)
The role of law enforcement in the process of enforcement of criminal justice law in Indonesia is very important to give birth to public order, legal certainty and a sense of justice for all Indonesians, including in the criminal acts of online prostitution. This research uses a type of sociological juridical socio legal approach study with the type of analytical descriptive research. The data used includes primary data and secondary data. The results of the study stated that the role of law enforcement against criminal online prostitution in DIY is done by the police, prosecutors and judiciary court in accordance with its duties and authorities in the legislation. The obstacles faced by law enforcement in the aid online prostitution in DIY are divided into 2 internal and external. Internal constraints include a lack of legal devices to ensnare actors PSK and users consumers online prostitution, a lack of police personnel who can immediately follow up the findings of cyber teams, the need for up to date equipment and personnel capabilities To compensate cyber crimes, the difficulty of completing evidence and witnesses for a court endowment and still a lack of socialization programs related to online prostitution as a preventative. External constraints include, a permissive community attitude toward online prostitution encountered, growing the market share of online prostitution, less friendly cooperation with other parties such as hotels or nightspots, as well as admin constraints or business operators of online prostitution are moved from outside Yogyakarta.